К проблеме применения технологий искусственного интеллекта в задачах развития городской инфраструктуры - Rashevskiy, N. M.; Dzhagaev, V. A.; Khoroshun, D. A.; Uchevatkin, M. D.; Akolzin, M. A. (Sot͡s︡iologii͡a︡ goroda, 2025)
Artificial intelligence is actively penetrating the urban development industry, offering new opportunities to optimize processes and improve efficiency. Machine learning, computer vision and big data analysis technologies allow for automated design, optimized urban development management, increased safety and reduced costs at all stages of the facility’s life cycle — from design to operation. However, widespread implementation of artificial intelligence faces challenges such as the need for standardization, cybersecurity and significant investment. The article discusses the advantages and disadvantages of using a probabilistic and deterministic approach to artificial intelligence for construction tasks and the formation of the architectural appearance of urban infrastructure facilities. An example of developing a knowledge base for an automated information system for laying out facing materials on the facades of city buildings is given